1994
DOI: 10.1021/bi00196a002
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Proton Resonance Assignments and Metal Cluster Topology of Lobster Metallothionein-1

Abstract: NMR studies of 111Cd6-MT 1 from lobster have been conducted to determine coordination structure of Cd-thiolate binding in the protein. Sequential proton resonance assignments were made using standard two-dimensional 1H NMR methods. Two-dimensional 1H-111Cd HMQC experiments were then carried out to determine the cadmium-cysteine connectivities in the protein. With this information, it was established that the six Cd ions exist in two different Cd3S9 clusters, each involving three bridging and six terminal thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…This is supported by the following observations: (a) a higher copper binding ability of ␤␤MTH than that of ␤␣MTH; (b) the comparable behavior of the crustacean and mammalian individual mutant domains; and (c) the capacity of MTH C-terminal domain to yield a minor Zn 4 species in vivo. The different Cd(II) connectivities reported for the C-terminal domains of Callinectes 1 and Homarus MT (11,12), despite sharing the number and position of cysteine residues, also supports the predicted flexibility of the crustacean ␤␣MT domain.…”
Section: Recombinant Synthesis and Characterization Of Zn-␤␤mth And Zsupporting
confidence: 56%
See 1 more Smart Citation
“…This is supported by the following observations: (a) a higher copper binding ability of ␤␤MTH than that of ␤␣MTH; (b) the comparable behavior of the crustacean and mammalian individual mutant domains; and (c) the capacity of MTH C-terminal domain to yield a minor Zn 4 species in vivo. The different Cd(II) connectivities reported for the C-terminal domains of Callinectes 1 and Homarus MT (11,12), despite sharing the number and position of cysteine residues, also supports the predicted flexibility of the crustacean ␤␣MT domain.…”
Section: Recombinant Synthesis and Characterization Of Zn-␤␤mth And Zsupporting
confidence: 56%
“…On the basis of their amino acid alignments, further application of the ␤/␣ domain terminology led to the consideration of crustacean peptides as ␤-␤ MT (10) and thus putative copper thioneins. This was corroborated by the three divalent ions contained in each domain of the crustacean Cd-MT structures solved by NMR (11,12) and thus comparable with the Cd 3 -␤MT fragment in mammalian MT.…”
supporting
confidence: 54%
“…However, the ability of S2ЈC receptors to coordinate Cd 2ϩ in both the native open and closed configurations of the receptor places a restriction on the maximal diameter the pore attains in both states. Using the length of the Cd-S bond (2.1-2.5 Å; (28,29,36,54)), the ionic radius of Cd 2ϩ (0.91 Å), and assuming 5-fold pseudosymmetry in the 5-HT 3A homopentameric receptor, we can estimate a maximum pore diameter of ϳ7 Å if coordination occurs across the receptor pore. If Cd 2ϩ is coordinated by sulfhydryl moieties on adjacent subunits, the pore diameter can be as wide as ϳ11 Å (using the Pythagorean theorem).…”
Section: Discussionmentioning
confidence: 99%
“…Previous structural studies carried out with lobster (Homarus americanus) and crab (Callincetes sapidus) Cd 6 -MT using 2D-NMR methods showed that the Cd-cysteine connectivities and, hence, the peptide folding, differ between their b N and b C clusters and also diverge from that found for the b N domain in mammalian MTs, despite the nearly homologous placement of cysteine residues in the crustacean and mammalian b N domains [17,18]. These three M 3 b domains display different reactivity toward reagents such as DTNB [5,5¢-dithio(2-nitrobenzoic acid)] and EDTA, leading to the hypothesis that their reactivity is related to the detailed folding of the peptide sequences around their clusters and not just to properties of the clusters themselves [19,20].…”
Section: Introductionmentioning
confidence: 95%
“…Crustacean MTs differ from the mammalian structure in that they only have 18 cysteine residues within their sequences that give rise to two M 3 S 9 clusters and peptide domains [16,17,18]. Previous structural studies carried out with lobster (Homarus americanus) and crab (Callincetes sapidus) Cd 6 -MT using 2D-NMR methods showed that the Cd-cysteine connectivities and, hence, the peptide folding, differ between their b N and b C clusters and also diverge from that found for the b N domain in mammalian MTs, despite the nearly homologous placement of cysteine residues in the crustacean and mammalian b N domains [17,18].…”
Section: Introductionmentioning
confidence: 99%